MON-518 Osteoporosis in a Young Adult with Trisomy 13 - Wynn, Anne (J Endocr Soc, 2019)
Background: Trisomy 13 is associated with multiple congenital anomalies, including cleft lip/palate, microcephaly, polydactyly, rocker bottom feet, iris coloboma, holoprosencephaly, seizures, heart defects, kidney malformations, respiratory distress, and feeding difficulties (1). It affects approximately 1 in 12,000 live births, and median survival time is 7-10 days, with a 5-year survival of 9.7%, although a few reports exist of survival into the second decade (2). Clinical Case: A 20-year-old male with trisomy 13 presented to endocrinology clinic for evaluation of osteoporosis. He was diagnosed with trisomy 13 by prenatal amniocentesis, confirmed by karyotype after birth. He has a history of Dandy-Walker malformation, holoprosencephaly, severe developmental delay, ventricular septal defect, dextrocardia, partial situs inversus, omphalocele, cleft lip and palate, pancreatitis, malposition of the duodenum, neurogenic bladder, gastrostomy tube dependence, left iris coloboma, scoliosis, and wheelchair dependence since age 12. Parents reported that he had no history of thyroid or adrenal dysfunction. He briefly received growth hormone injections, but these were stopped by the parents. On physical exam, he had buried micropenis and one palpable testis, 3-4 mL. DXA scan showed severe reduced bone mineral density of the lumbar spine (L1-L4) with Z score of -9.6. Radiography of the spine revealed compression deformities of thoracic vertebrae 3, 4, and 11. Serum calcium was 9.7 mg/dL (8.4 - 10.2 mg/dL), and phosphorus level was 4.8 mg/dL (3.1 - 5.6 mg/dL). Vitamin D level was 48.2 ng/ml (30.0 - 70.0). The patient had a low-trauma fracture of the left foot in 2011. MRI of the brain showed a grossly normal appearing pituitary gland. Laboratory studies were obtained, including TSH 2.270 mcIU/mL (0.358 - 3.740 mcIU/mL); free T4 1.44 ng/dL (0.80 - 2.00 ng/dL); LH 0.104 IU/L (1.5 - 9 IU/L); FSH 0.974 IU/mL (2.0 - 9.2 IU/mL); total testosterone <2.5 ng/dL (264 - 916 ng/dL); free testosterone <0.2 pg/mL (52-280 pg/mL); IGF-1 64 ng/mL (281-510 ng/mL); IGF-BP3 antibody 3.62 mg/L (2.72 - 6.36 mg/L). The patient had multiple risk factors for osteoporosis, including hypogonadism, growth hormone deficiency, and non-ambulatory status. He was prescribed testosterone cypionate. Follow up was planned for 4 months after the initial visit. Conclusion: Our case reporting osteoporosis in Trisomy 13 is unique, with no other case reports describing this syndrome found in the literature. This is likely due to his unusual prolonged survival. References: (1) Bruns DA, Campbell E. 2014. Nine children over the age of one year with full trisomy13: A case series describing medical conditions. Am J Med Genet Part A 164A:2987-2995. (2) Meyer RE et al. Survival of children with trisomy 13 and trisomy 18: A multi-state population-based study. Am J Med Genet A. 2016 Apr;170A(4):825-37.